Pendidikan, Ekspektasi Usaha, Skala Usaha dan Pengalaman Usaha Terhadap Penggunaan Informasi Akuntansi di UKM Kota Jayapura - Fitri; Fajar Rina Sejati (JURNAL ECONOMINA, 2024)
This  research  aims  to  examine  the  influence  of  education,  business  expectations,  business  scale  and  business  experience  on  the  use  of  accounting  information.  This  research  used  data  from  96  respondents  from  SMEs  in  Jayapura  City.  The  research  method  used  in  this  research  is  the  purposive  sampling  method,  and  uses  SPSS  21  as  analysis  software.  The  data  analysis  technique  uses  multiple  regression  analysis.  The  research  results  show  that  business  expectations  and  business  scale  do  not  influence  the  use  of  SME  accounting  information  in  Jayapura  City.  Meanwhile,  education  and  business  experience  positively  influence  the  use  of  accounting  information  in  SMEs  in  Jayapura  City.